Sensory Deprivation and Psychiatric Disorders: Association, Assessment and Management Strategies. Issue 5 (September 2021) - Sahoo, Swapnajeet; Naskar, Chandrima; Singh, Ajaypal; Rijal, Rika; Mehra, Aseem; Grover, Sandeep
Background: Sensory deprivation (SD) is a widely prevalent condition that leads to various health-related consequences and is also an important cause of disability worldwide. Earlier, SD experiments were used as research modalities to alter human behavior. In recent years, the focus has shifted to understand how SD can affect the mental health of individuals (with congenital or acquired sensory impairments). This narrative review focuses on the current understanding about the association of SD and psychiatric disorders. Methods: A comprehensive literature search was done PubMed, Scopus, PsycINFO, and Google Scholar and in the cross-references of relevant articles. Keywords included "sensory deprivation, " "blindness, " "deafness, " "mental illness, " "psychiatric disorders, " "prevalence, " "assessment, " and "management" in various combinations. Only original articles (abstract and full text) published in English till October 2020 were included. Results: The prevalence of anxiety, depression, dementia, suicidality, and psychosis in persons with SD is higher than the general population (highest being in persons with dementia with comorbid SD). Several mechanisms/hypotheses have been proposed to explain these associations. Assessment of SD includes a thorough history taking, with adequate awareness about the difficulties faced during a psychiatric interview in this population. Modifications in the psychometric assessment procedures are warranted. Management depends on a multi-disciplinary approach that includes proper referral to specialties, pharmacological management (depending on diagnosis as well as taking care of ototoxic/ocular side-effect profile of the drugs), and nonpharmacological supportive measures. Conclusions: SD is a complex condition, and evidence suggests that persons with SD have higher psychiatric morbidity. A comprehensive assessment, along with holistic management approach is warranted.